(3GdETGQGJ hGdJfHjgGJ aj GdefWb hGdMceIs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3jHOC HGdfgL GdChd ai ZQV GdefWb GdeQGO ef GdefWb Gf jchf YfO GdGfSGf Gdg bGfhfjI JYUefg eQGYGJgG Yf Gf jVd ai acQg s
(3BNQgG (B:s
(3hYGgOg HGddg hHCeGf dG eNGQL dgG djLQi ajeG JDJjg eLQGc aEf GPYJ gPG GdYde hGVYJg HGddg Hjfi hHjfc hcai Hg hcjdG s
(3GdfSNI HgG MhGTs
(3cJHJ HYV GdCdaGX HGdMeQIs
(3fSNI KGdKI s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdadSaI hGdefWbs